The impact of the African continental Free Trade Agreement: A continentwide macroeconomic assessment and distributional analysis in Nigeria and Rwanda - Traoré, Fousseini; Mamboundou, Pierre; Diop, Insa; Sy, Abdourahmane (International Food Policy Research Institute, 2025)
Africa remains the least open continent in the world, with high trade restrictions for both intra- and extra-African partners. These restrictions include both tariff and nontariff measures, as well as high transportation costs due to poor infrastructure. However, previous studies have highlighted the crucial role of intra-regional trade in boosting national economies, promoting development, and enhancing food security by increasing the availability of food and stabilizing domestic markets. In particular, informal cross-border trade, which is pervasive in Africa, contributes to food security, although further research is needed on its magnitude.